P.Lips. Inv. 1228 und 590: Eine neue ägyptische Königsliste in griechischer Sprache - Popko, Lutz (Zeitschrift für ägyptische Sprache und Altertumskunde, 2011)
Discussion of two recently published fragmentary Greek papyri from Leipzig, dating into the 2nd century AD. The text contains a non-Manethonian king-list with some monarchs of the Third Intermediate and the Late Period as well as a reference on the oracle of the lamb.